Density functional theory study of thermodynamic and kinetic isotope effects of H2/D2 dissociative adsorption on transition metals. Issue 13 (13th June 2018) - Bai, Yunhai; Chen, Benjamin W. J.; Peng, Guowen; Mavrikakis, Manos
Abstract : Thermodynamic/kinetic isotope effects for H2 /D2 dissociative adsorption calculated on metal surfaces offer a means to identify active sites. Abstract : We studied the thermodynamic isotope effects (TIEs) and kinetic isotope effects (KIEs) for H2 /D2 dissociative adsorption using periodic, density functional theory (DFT)-based calculations. We examined the TIEs on the close-packed, open, and stepped surfaces, of twelve transition metals (Fe, Co, Ni, Cu, Ru, Rh, Pd, Ag, Re, Ir, Pt, and Au), and the KIEs on the surfaces of three noble metals (Cu, Ag, and Au). Both TIEs and KIEs were evaluated at 1/9 ML coverage. We find distinct TIEs on different adsorption sites, indicating that TIEs could be used in conjunction with binding energies to determine the dominant adsorption sites for hydrogen. Additionally, we find that while H2 dissociative adsorption may traditionally be considered structure insensitive in terms of reaction rates, it can exhibit structure sensitivity in terms of its KIEs. Complementarily to TIEs, KIEs might therefore be useful for identifying active sites for H2 dissociative adsorption on the three noble metal transition metal catalysts studied.